How well does the social safety net work? : the incidence of cash benefits in Hungary, 1987-89 - Van de Walle, Dominique; Ravallion, Martin; Gautam, Madhur (Washington, D.C. : World Bank, 1994)
Seemingly high levels of public spending on cash benefits to households in Hungary, and the heavy reliance on programs which do not explicitly restrict eligibility to the poor, has led to reforms aimed at improved targeting. The incidence of cash benefits is examined here using a new panel data set for 1987-89, constructed for the purposes of this study from the Hungarian Household Budget Surveys for those years.
Includes bibliographical references: p. 80-82.
ne 18/03/2019
Loans
Keywords: Economic assistance, Domestic; Public welfare; Poverty; Social conditions; Hungary